Influence of service quality, moral obligations and tax sanctions on compliance - Dela Oktaviani Putri; Ardiani Ika Sulistyawati (Inovasi Analisis Data, 2024)
Purpose – This research aims to investigate the effect of service quality, tax sanctions, and moral obligation on hotel taxpayer compliance. In the backdrop of an evolving tax landscape, having knowledge of these determinants is essential for enhancing voluntary compliance and developing effective tax administration policies.Design/methodology/approach – The paper follows a quantitative approach with multiple regression analysis. A structured survey was used to collect data from hotel taxpayers, and various statistical tests were performed to ensure the robustness of the model, including testing for normality, multicollinearity, and heteroskedasticity.Findings – The findings suggest that service quality plays a significant role in taxpayer compliance and emphasises the need for effective tax administration as a means of promoting voluntary compliance. However, tax punishment and moral suasion fail to make a dent, which means sticks and carrots alone do not sway the taxpayer.Originality/value – This paper adds to the literature by offering empirical evidence on the determinants of hotel taxpayer compliance and the role of service-oriented tax administration. The findings are at odds with enforcement-centered approaches and call for policy changes towards trust building and service improvement strategies.Research Implications – The paper highlights the importance of taxpayer service and engagement; skills that should be weighted over punishment in the eyes of tax authorities. Future research should study digital tax administration and behavioral interventions to increase compliance even more